1969
DOI: 10.1017/s002193200000715x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the sex ratio at birth in Australia, 1902–65

Abstract: Using Australian records of human births for the first six decades of the twentieth century, the proportions of male and female births are studied in relation to the mother's age, the father's age, the parents' ages in combination, and certain other factors. The principal data used relate to the years 1931-55, during which over 3 million children were born, yet even so the significant features are not easy to discern.Masculinity tends to fall as the age of either parent increases. But it is only average or bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1971
1971
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Our study indicated that multiple births have a lower sex ratio than singletons, which was consistent with results from the previous studies [ 31 , 38 , 39 ]. In addition, we demonstrated a higher rate of stillbirths in males among multiple births.…”
Section: Discussionsupporting
confidence: 93%
“…Our study indicated that multiple births have a lower sex ratio than singletons, which was consistent with results from the previous studies [ 31 , 38 , 39 ]. In addition, we demonstrated a higher rate of stillbirths in males among multiple births.…”
Section: Discussionsupporting
confidence: 93%
“…Pollard (1969) studied the sex radio in Australia, 1902-1965, McMahan (1951 in the United States, 1915-1948, and Seki (1968 in England and Wales, 1900-1965, and in France, 1900-1964. The regression coefficients of the sex ratio on year in Australia during the period from 1902 to 1976 (Sources: Pollard, 1969; Official Year Book of The Commonwealth of Australia, 1969;Births, 1976) , 1973;Monthly Vital Statistics Report, 1976), and 0.000101+0.000007, respectively. These values are significant at the 1~, 5~, and 1~ levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These two examples predict opposite trends for human sex ratios with maternal age. Empirical studies have alternatingly found sex ratios to increase (Takahashi ), decrease (Pollard ; James and Rostron ), or be uncorrelated with maternal age (Almagor et al. ; Jacobsen et al.…”
Section: Case 1: Maternal Agementioning
confidence: 99%
“…These two examples predict opposite trends for human sex ratios with maternal age. Empirical studies have alternatingly found sex ratios to increase (Takahashi 1954), decrease (Pollard 1969;James and Rostron 1985), or be uncorrelated with maternal age (Almagor et al 1998;Jacobsen et al 1999). These mixed results may suggest that the effects of various offspring costs vary or even counterbalance in different populations, or that there are additional factors at play.…”
Section: Case 1: Maternal Agementioning
confidence: 99%